(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yusran Y, Erniwati E, Wahyuni D, Ramadhanil R, Khumaidi A. 2021. Diversity of macro fungus across three altitudinal ranges in Lore Lindu National Park, Central Sulawesi, Indonesia and their utilization by local residents. Biodiversitas 22: 199-210. A large amount of biodiversity research has been carried out in Lore Lindu National Park, a major biodiversity center in Central Sulawesi, Indonesia, but none have investigated the biodiversity of macrofungi and their traditional utilization. Therefore, this study aimed to explore the diversity of macro fungus in Lore Lindu National Park, and to identify their potential uses as food sources and medicinal uses by the local residents living around Lore Lindu National Park. Exploration of macrofungus species in Lore Lindu National Park was done at three locations representing three altitudinal ranges: (i) <500 m above sea level (asl); (ii) 500–1500 m asl; and >1500 m asl. Ten plots were placed in two major lines with a 100 m distance between plots in each sampling location. All macrofungi within the observation plots were then documented and identified. Ethnomycological studies were done by asking questionnaire to selective respondents, group discussion, and pictorial presentation studies to random respondents in five villages located in the buffer zone of the national park area. This study found 172 species (including unidentified species/sp.) from 33 families of macro fungus in Lore Lindu National Park in which 159 of them belong to the Basidiomycota division, while 13 of them were of the Ascomycota division. Our results also showed varying diversity of macrofungus at different altitudes. At the elevation of <500 m asl, as many 77 species were found, while 117 and 142 species were found at the elevation of 500-1500 and >1500 m asl, respectively. Marasmius spp and Hygrocybe spp were the most abundant genera, and nine species (i.e. Schizophyllum commune, Termytomyces sp, Auricularia auricular-judge, Auricularia sp., Pleurotus ostreatus, Ganoderma lucidum, Xylaria sp., Agaricus sp. dan Lentinus sajor-caju) were utilized as a food source and in traditional medicine by the residents around the national park area.